Optimalisasi Proses Degumming Minyak Biji Ketapang Menggunakan Asam Fosfat dan NaOH sebagai Bahan Baku Biodiesel - Syabriyana, Maliya; Zeni Ulma; Ais Shenly Eka Putri Vinzani (Jurnal Serambi Engineering, 2024)
Ketapang seeds (Terminalia catappa) are a potential source of vegetable oil as a feedstock for biodiesel production. However, the use of ketapang seed oil remains very limited. Degumming is a crucial step in biodiesel production as it determines the quality of the raw material preparation. Various methods can be used to remove gum, including heating and the addition of acids (H3PO4, H2SO4 and HCl) or bases (NaOH). The aim of this study is to maximise the quality of biodiesel feedstock by improving the degumming efficiency using different concentrations of phosphoric acid (H3PO4) and NaOH. The phosphoric acid concentrations used were 0.5%, 1% and 1.5% v/v and the NaOH concentrations were 0.5%, 1% and 1.5% w/w. The degumming process was carried out at 80 °C with stirring for 30 min at each stage. After degumming, ketapang oil has excellent clarity compared to before treatment. Based on the research conducted, the optimum degumming conditions were found at a phosphoric acid concentration of 0.5% v/v and a NaOH mass of 1% w/w, resulting in an FFA content of 0.4% and a density of 902.5 kg/m³.